Unlocking the Potential of Spent Mushroom Substrate (SMS) for Enhanced Agricultural Sustainability: From Environmental Benefits to Poultry Nutrition - Filipa Baptista; Mariana Almeida; Jéssica Paié-Ribeiro; Ana Novo Barros; Miguel Rodrigues (Life, 2023)
In this comprehensive review, we delve into the myriad applications of spent mushroom substrate (SMS) in agricultural contexts, with a particular emphasis on its role in fostering sustainable poultry production. Our examination spans three key domains: the use of SMS in fertilizers, its impact on environmental factors and gas emissions, and its contribution to poultry nutrition. This review synthesizes findings from multiple studies that underscore the potential of composted SMS as a viable alternative to conventional inorganic fertilizers, effectively meeting crop nutrient needs while mitigating groundwater contamination risks. Moreover, we highlight the substantial environmental advantages associated with the utilization of SMS and poultry waste, including reductions in greenhouse gas emissions and the promotion of sustainable waste management practices. Additionally, we explore the promising outcomes of integrating SMS into animal feed formulations, which have demonstrated significant enhancements in livestock growth performance and overall health. In sum, this review underscores the versatility and untapped potential of SMS as a valuable agricultural resource, with a particular focus on its role in advancing sustainable practices, optimizing nutrient management, and harnessing the value of organic waste materials, especially in the context of poultry production.